The Amber Road in Poland. State of research and perspectives - Błażejewski, Artur (Archaeologia Lituana, 2011)
The study of what is known as the Amber Road has a long tradition in Poland and few others countries, as Lithuania. It seems that this concept is now well-rooted in Polish literature, not only archaeological and historical, but also in works of fiction, one may say, in culture at large. Obviously, at times, its popular perception is quite far removed from scientific findings nevertheless, in the archaeology of the Barbaricum it will continue as one of the leading subjects of research. [...]